Assessing core body temperature in a cool marathon using two pill ingestion strategies - Grivas Gerasimos V.; Muniz-Pardos Borja; Guppy Fergus; Pitsiladis Asimina; Bundy Ross; Miller Mike; Fitzpatrick Daniel; Richardson Alan; Hodgson Luke; Leckie Todd; Stacey Mike; Racinais Sebastien; et al. (Translational Exercise Biomedicine)
The purpose was to directly assess in-competition thermoregulatory responses in recreational runners during a city marathon conducted in cool, ambient conditions using a two-pill ingestion strategy.